2017
DOI: 10.1002/ppul.23668
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization predicts asthma development among wheezing toddlers in secondary healthcare

Abstract: Sensitization to inhalant allergens is a strong predictor of school age asthma in secondary healthcare and has added predictive value when combined with non-invasive determinants. Pediatr Pulmonol. 2017;52:729-736. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…İnhalan allerjen duyarlılığı sıklığı sık hışıltı grubunda daha yüksekti. Sık hışıltı atakları olan infantlarda atopi ve inhalan allerjen duyarlılığının ileriki yıllarda astım gelişimini öngörmede önemli bir değere sahip olduğu bilinmektedir (34).…”
Section: Discussionunclassified
“…İnhalan allerjen duyarlılığı sıklığı sık hışıltı grubunda daha yüksekti. Sık hışıltı atakları olan infantlarda atopi ve inhalan allerjen duyarlılığının ileriki yıllarda astım gelişimini öngörmede önemli bir değere sahip olduğu bilinmektedir (34).…”
Section: Discussionunclassified
“…Population studies from the USA and Europe report that half of all children at age 6 have experienced wheezing during their lifetimes [5] and that one in three children has at least one episode of wheezing before their third birthday [6]. Approximately 40% of preschoolers who wheeze show respiratory symptoms later in their childhood, although there is variation from 22% to 55% [7][8][9]. Despite the high incidence and prevalence, there are knowledge gaps regarding the mechanisms of disease pathogenesis and the optimal treatment of wheezing disorders in preschool children.…”
Section: Prevalence Of Wheezing Disordersmentioning
confidence: 99%
“…2.4) was highly predictive of later asthma at preschool age both in a secondary healthcare and research setting [8]. IgE measurement can be used as a way of differentiating between high-and lower-risk patients (86% vs 45% risk of asthma development when measuring airborne allergen sensitization) as well as in choosing possible therapeutic measures [9]. Predictors may, however, change according to wheezing phenotype or debut age, reflecting the natural variance of wheezing [8,137].…”
Section: Attempts At Early Prediction Of (Severe) Asthmamentioning
confidence: 99%
“…Wheezing is common in early childhood, and prognosis in these children for future diagnosis of asthma is an important issue. Boersma et al 1 reported that sensitization to inhalant allergens in preschoolers is a significant predictor of school age asthma, with positive and negative predictive values of 86% and 55%, respectively, in a study of 116 children who presented to specialists for evaluation of early wheezing.…”
Section: Asthmamentioning
confidence: 99%
“…Wheezing is common in early childhood, and prognosis in these children for future diagnosis of asthma is an important issue. Boersma et al reported that sensitization to inhalant allergens in preschoolers is a significant predictor of school age asthma, with positive and negative predictive values of 86% and 55%, respectively, in a study of 116 children who presented to specialists for evaluation of early wheezing. Multivariate analysis showed that sensitization to inhalant allergens (house dust mite, cat, dog, pollen, or mold) also increased the area under ROC curve for noninvasive predictors such as eczema in the first year of life, and hospital admission in the first 3 years of life.…”
Section: Introductionmentioning
confidence: 99%